2014
DOI: 10.12693/aphyspola.125.348
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured W-Cu Electrical Contact Materials Processed by Hot Isostatic Pressing

Abstract: Nanostructured W Cu Ni electrical contact materials to be used in low voltage vacuum switching contactors for nominal currents up to 630 A were developed successfully by hot isostatic pressing. W Cu Ni composite powder mixtures with copper content of 20 to 40 wt% and 1 wt% Ni were mechanically alloyed in Ar atmosphere by high--energy ball milling with a ratio of milling steel balls: powders mixtures of 8:1 and rotation speed of 400 rpm for 10 and 20 h. The e ect of mechanical alloying on the sintering response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…W-Cu materials are of a major interest for thermal-electrical applications like electrical contacts used in low voltage (LV), medium voltage (MV) and high voltage (HV) switching devices working in vacuum, sulfur hexafluoride (SF 6 ) gas or oil [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…W-Cu materials are of a major interest for thermal-electrical applications like electrical contacts used in low voltage (LV), medium voltage (MV) and high voltage (HV) switching devices working in vacuum, sulfur hexafluoride (SF 6 ) gas or oil [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…W-Cu composites are considered as pseudo-alloys and advanced engineering materials due to their specific physical, electrical, thermal and mechanical properties. W-Cu powder mixtures are produced by various methods, from which the common methods are mechanical mixing, mechanical alloying and high energy ball milling of elemental powders in dry or wet conditions [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of switching directly affects the operational reliability and the life of the switchgear [1][2][3] . With a rapid development of the modern industry, especially the electrical and electronic industry, switch electrical appliances are developing in the direction of high current, miniaturization, high voltage and long life, and the arc extinguishing performance and anti-erosion performance of the contact materials and contact systems are proposed higher requirements [4][5][6] . The ideal contact materials should have excellent electrical conductivity, thermal conductivity, anti-fusion welding, resistance to material transfer, arc erosion resistance and low and stable contact resistance 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, second phase is added to improve the arc extinguishing performance of the contact or improve the viscosity of the molten pool to reduce the melt splashing. In recent years, many researchers have modified the microstructure and electrical contact properties of Cu alloys by adding different elements (W, Ni, Ag, Ce, Y, Cr) 1,5,12,15,16 or oxides (CdO, SnO 2 , CeO 2 ) 9,11,17 . Among these, the action of some oxides is more significant and effective to electrical contact properties than that of elements.…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that there was a meaningful relationship between the sinterability and milling time; higher hardness and conductivity were obtained by prolonged MA and SPS due to lower W-W contiguity of MA powders, a decrease in the melting point of Cu up to 145˚C was achieved and a more homogeneous distribution of Cu prevented the formation of Cu pool during liquid phase sintering thereby increasing the homogeneity of the sintered compacts. A study of nanostructured W-Cu electrical contact materials processed by hot isostatic process was carried out by Tsakiris et al [21]. In their study, W-Cu-Ni with Cu content ranging from 20 -40 wt% and 1 wt% Ni were mechanically alloyed for 10 and 20 h, and they achieved a high sintered density of 89% and homogeneous microstructure, higher Vickers hardness values were obtained from the compacts produced from the powders milled for 20 h due to the reduced particle size, uniform distribution of the intermetallic phases as well as the presence of W which was the harder phase.…”
Section: Introductionmentioning
confidence: 99%